First-principles study of structural, electronic, and optical properties of GaAs (001)- (2x4) with surface defects - Bacuyag, Dhonny P. (Animo Repository, 2023)
First-principles calculations in understanding the geometrical, electronic, and optical properties of GaAs (001)- β2(2x4) and GaAs (001)- β(2x4) with defects are performed in the framework of density functional theory (DFT) and are implemented in the Vienna ab initio simulation package (VASP). The surface point defects that are investigated are As antisite (AsGa), Ga antisite (GaAs), and Ga vacancy (GaV). In this study, the main objective is to provide insights on the distinguishing effects of surface point defects by providing the correlation between structural changes due to the defects and the consequent electronic and optical properties. It identified stable defects that led to mid-gap states, in the hope of clarifying the possibility of two-step photon absorption mediated by midgap states observed experimentally in low-temperature GaAs (LT-GaAs) when used in a photoconductive antenna (PCA). An investigation on the photo-absorption is conducted to provide helpful insights for its application in efficient, low cost, and stable photoconductive emission and detection of terahertz (THz) radiation. For the structural properties with point defects (AsGa, GaAs, and Gav), the AsGa demonstrated the greatest stability with the calculated negative formation energies. The locations of point defects that set out the greatest stability were established. Significant changes in the geometrical structure of clean structures, in the incorporation of these point defects were presented. With respect to the electronic properties, the structural distortions upon introduction of point defects greatly influenced the band structure, density of states (DOS) and the charge density distribution. DOS and band structure calculations on GaAs (001)- β2(2x4) revealed that AsGa, GaAs, and GaV induced an energy gap of 0.97 eV, 0.52 eV, and 0.82 eV which are characteristics of the EB3, EL4, and EL2 deep level defects in experiments. For GaAs (001)- β(2x4), it was revealed that the introduction of point defects created deep energy levels characteristic of EL16 (0.37 eV), EL5 (0.46 eV), and EL2 (0.71 eV) for AsGa, GaAs, GaV, respectively. Based on the results of partial densities of states and the partial charge density distribution, these induced sub-bands and midgap states originate from point defects and the neighboring atoms. These midgap states are proposed to enable below band gap excitation of electrons. The optical properties are found to be greatly linked to electronic properties. The different band gap energies with the presence of midgap and subbands for the different point defect structures resulted in distinct imaginary and real dielectric functions. This eventually led to distinct optical properties like absorption coefficients, coefficient of extinction, refractive index, and reflectivity. The absorption of incident photons for energies below the known bulk band gap energy is confirmed. Certainly, the defects altered the geometrical structures, which changed the electronic structures, and determined the optical properties. The results of this study therefore serve as groundwork and give us design guidelines on a wide range of applications from the low energy THz to a higher energy spectrum. Keywords: LT-GaAs, Terahertz, Density Functional Theory, Point Defects, Midgap States, Subband-gap